Forming of stamped metal products and creation of laboratory equipment - Kuzembayev Серік; Alzhanov Марат; Tuleuova Гульмаржан; Tuleu Бектұрсын (Рroblems of engineering and professional education, 2023)
The paper presents the design and operation of various devices for the molded metal. The features of the technology of manufacturing method of pressing of the crushed material, as well as developed press design using false cylinder, which reduces the friction between the die wall and the particles of the powder, as well as giving ravnovernoe distribution of the powder particles, whereby we obtain the same density in all parts of the molded metal.